Lithium Bonds in Lithium Batteries - Chen, Xiang; Bai, Yun‐Ke; Zhao, Chen‐Zi; Shen, Xin; Zhang, Qiang (Angewandte Chemie International Edition, 2020)
Lithium bonds are analogous to hydrogen bonds and are therefore expected to exhibit similar characteristics and functions. Additionally, the metallic nature and large atomic radius of Li bestow the Li bond with special features. As one of the most important applications of the element, Li batteries afford emerging opportunities for the exploration of Li bond chemistry. Herein, the historical development and concept of the Li bond are reviewed, in addition to the application of Li bonds in Li batteries. In this way, a comprehensive understanding of the Li bond in Li batteries and an outlook on its future developments is presented. Lithium bonds that are present in lithium batteries are discussed in this Viewpoint, including historical developments, comparisons with hydrogen bonds, and their potential applications. Discourse on the chemistry of the Li bond can provide fruitful insight into the fundamental interactions within Li batteries and thus deliver a deeper understanding of their working mechanism.